2018
DOI: 10.1021/acs.est.7b04343
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Structural Defects on Biomineralized ZnS Nanoparticle Dissolution: An in-Situ Electron Microscopy Study

Abstract: The dissolution of metal sulfides, such as ZnS, is an important biogeochemical process affecting fate and transport of trace metals in the environment. However, current studies of in situ dissolution of metal sulfides and the effects of structural defects on dissolution are lacking. Here we have examined the dissolution behavior of ZnS nanoparticles synthesized via several abiotic and biological pathways. Specifically, we have examined biogenic ZnS nanoparticles produced by an anaerobic, metal-reducing bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 60 publications
(125 reference statements)
4
48
0
Order By: Relevance
“…This suggests that surface interaction with surrounding compounds influences ZnS NPs structure. Eskelsen et al (2018) also observed structural defaults (twins) on the (111) face of biogenic ZnS NPs, to a lower extent because of the unfavorable particles's orientation. The authors detected carbon traces in biogenic ZnS NPs aggregates and assumed a microbial metabolite interaction with ZnS NPs.…”
Section: Structural Properties Of Biogenic Zns Npsmentioning
confidence: 94%
See 2 more Smart Citations
“…This suggests that surface interaction with surrounding compounds influences ZnS NPs structure. Eskelsen et al (2018) also observed structural defaults (twins) on the (111) face of biogenic ZnS NPs, to a lower extent because of the unfavorable particles's orientation. The authors detected carbon traces in biogenic ZnS NPs aggregates and assumed a microbial metabolite interaction with ZnS NPs.…”
Section: Structural Properties Of Biogenic Zns Npsmentioning
confidence: 94%
“…Regarding ZnS NPs, Xu et al (2016) highlighted by electronic microscopy that biogenic ZnS NPs dissolution starts where the structural defects are observed. Also, Eskelsen et al (2018) have calculated a higher surface energy for biogenic ZnS NPs, compared with the abiotic ones, suggesting a higher reactivity. In contrast, smaller abiotic ZnS NPs have a higher available specific surface area for oxidative dissolution.…”
Section: Structural Properties Of Biogenic Zns Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact ZnS dissolved preferably when it is shelled over CdSe than when it is the sole constituent of a nanoparticle can arise from the fact ZnS is likely to have more defects if it is grown over materials with different epitaxies (CdSe and CdS), as it has been shown by others. 42 However, the difference between CdSe and ZnS is greater than that between CdS and ZnS. Therefore, the alloyed shells may decrease dissolution.…”
Section: Cdse/zns-peiande3p Dissolution In Response To Ph and Oxygenmentioning
confidence: 99%
“…Shape, size, and surface coating of (nano)particles were also shown to affect binding of the particles to E. coli and Helicobacter pylori (Westmeier et al ., 2018). Reaction rates are controlled by the density of defects on the surface, which can lead to higher reaction rates for defect‐rich nanoparticles compared to defect‐poor nanoparticles (Eskelsen et al ., 2018). Lastly, it has been suggested that the binding efficiency of the same nanoparticle to microbes may differ depending on the bacterial species (discussed in Stauber et al ., 2018) and the bacterial growth state (Eymard‐Vernain et al ., 2018).…”
Section: Future Directionsmentioning
confidence: 99%